Exploring Ethnomethodology: A New Framework for Analyzing Human Resource Practices - Kurniawan, Fajar Azmi; Mukhlis, Imam; Zagladi, Arief Noviarakhman; Pyng, How Shwu (Pascasarjana UM, 2024)
This article presents a literature study that examines the use of ethnomethodology as an approach in qualitative research, specifically within the context of human resource management (HRM). Employing the Systematic Literature Review (SLR) method, this study explores, identifies, investigates, evaluates, and interprets existing research to uncover how ethnomethodology addresses challenges in HRM. The findings reveal that ethnomethodology offers a valuable lens for understanding complex issues within HRM by analyzing the everyday interactions and practices of individuals in the workplace. This approach enables researchers to uncover underlying problems in HRM and provides insights that can inform strategies for problem-solving. By highlighting the actions and knowledge of actors within organizations, ethnomethodology contributes to a deeper understanding of HRM dynamics, facilitating evidence-based solutions to improve management practices.